Work climate and performance of pharmaceutical chemists professionals in a sanitary products establishment in Lima, Peru, 2022 - Salvador Rivera, Gladys Isabel (2024)
Objective. To evaluate the relationship between the work climate and the performance of pharmaceutical chemists professionals in a sanitary products laboratory of Lima (Peru), 2022. Materials and methods. The study had a quantitative approach, was of type observational, cross-sectional, and counted with a descriptive non-experimental design. The sample was of 65 pharmaceutical chemists professionals. Two validated questionnaires were applied to measure the work climate and performance of pharmaceutical chemists using the Likert scale. Likewise, Cronbach's alpha was used to measure the reliability of the instruments. In the correlational analysis, Spearman's rho test was applied. Results. A significance of 0.05 was found; a p < 0.05 (p = 0.000) for the correlation analyses of the work climate – ​​job performance (p = 0.906) and for the analyses of the dimensions work climate – ​​efficiency (p = 0.863), work climate – ​​effectiveness (p = 0.859) and work climate – ​​quality (p = 0.893) of the performance of pharmaceutical chemists, respectively. Conclusion. There is a significant relationship between the work climate and performance of pharmaceutical chemists with a Spearman correlation coefficient (p = 0.906) to the 0.05 of significance, and a p = 0.00 < 0.05; as well as between the work climate and the dimensions efficiency, effectiveness, and quality of performance that these provide.